SPATIAL ANALYSIS OF MANGROVE DENSITY AND ITS EFFECT ON MACROZOOBENTHOS IN TEKKOLABBUA, SOUTH SULAWESI. - Ramadhani, Razkiyah; Saru, Amran; Faizal, Ahmad (Hasanuddin University, 2023)
This study aims to detect changes in mangrove cover using 30-meter resolution Landsat imagery in 2019 and 2021 and analysis of changes in density to macrozoobenthos abundance. The research method used is the analysis of satellite imagery with NDVI transformation integrated with field surveys, the relationship between mangrove density and abundance of macrozoobenthos was tested by regression analysis. The results showed that in 1 decade (2009-2021) there was an improvement in the quality of the mangrove ecosystem with an increase in the cover of the mangrove ecosystem by 5.49 Ha, which was accompanied by an increase in mangrove density. Improvement of ecosystem conditions also affects the increase in the abundance of macrozoobenthos in substrates, roots, and stems in mangrove ecosystems even though with a small coefficient of determination.